Statistical analysis of the effect of CME-diesel blends on the performance of a light duty common rail direct injection engine - Denoga, Gerald Jo C. (Philippine Engineering Journal)
This paper presents the effect of coconut methyl ester (CME) biodiesel blends in the performance of a light duty automotive common rail direct injection engine. Total of six fuel blends - B0 (Neat Diesel), B2 (2%CME, 98%B0), B5 (5% CME, 95%B0), B10 (10%CME, 90%B0), B15 (15%CME, 85%B0) and B20 (20%CME, 80% B0) were tested for performance at 100% load with varying speeds from 800 RPM to 2400 RPM at an interval of 400 RPM. At this typical engine speed range, no significant differences for biodiesel blends versus neat diesel were observed for torque.